Polysomnographic Outcomes After Observation for Mild Obstructive Sleep Apnea in Children Younger Than 3 Years. (29th September 2020) - Sarber, Kathleen M.; von Allmen, Douglas C.; Tikhtman, Raisa; Howard, Javier; Simakajornboon, Narong; Yu, Wenwen; Smith, David F.; Ishman, Stacey L.
Abstract : Objective: Mild obstructive sleep apnea (OSA), particularly in young children, is often treated with observation. However, there is little evidence regarding the outcomes with this approach. Our aim was to assess the impact of observation on sleep for children aged <3 years with mild OSA. Study Design: Case‐control study. Setting: Pediatric tertiary care center. Methods: We reviewed cases of children (<3 years old) diagnosed with mild OSA (obstructive apnea‐hypopnea index, 1‐5 events/h) who were treated with observation between 2012 and 2017 and had at least 2 polysomnograms performed 3 to 12 months apart. Demographic data and comorbid diagnoses were collected. Results: Twenty‐six children met inclusion criteria; their median age was 7.2 months (95% CI, 1.2‐22.8). Nine (35%) were female and 24 (92%) were White. Their median body mass index percentile was 39 (95% CI, 1‐76). Comorbidities included cardiac disease (42.3%), laryngomalacia (42.3%), allergies (34.6%), reactive airway disease (23.1%), and prematurity (7.7%). The obstructive apnea‐hypopnea index significantly decreased from 2.7 events/h (95% CI, 1‐4.5) to 1.3 (95% CI, 0‐4.5; P =. 013). There was no significant improvement in median saturation nadir (baseline, 86%; P =. 76) or median time with end‐tidal carbon dioxide >50 mm Hg (baseline, 0 minutes; P =. 34). OSA resolved in 8 patients (31%) and worsened in 1 (3.8%). Only race was a significant predictor of resolution per regression analysis; however, only 2 non‐White children were included. Conclusion: In our cohort, resolution of mild OSA occurred in 31% of patients treated with 3 to 12 months of observation. The presence of laryngomalacia, asthma, and allergies did not affect resolution. Larger studies are needed to better identify factors (including race) associated with persistent OSA and optimal timing of intervention for these children. Level of Evidence: 4.